PcG-mediated higher-order chromatin structures modulate replication programs at the Drosophila BX-C. - Federica Lo Sardo; Chiara Lanzuolo; Federico Comoglio; Marco De Bardi; Renato Paro; Valerio Orlando (PLoS Genetics)
Polycomb group proteins (PcG) exert conserved epigenetic functions that convey maintenance of repressed transcriptional states, via post-translational histone modifications and high order structure formation. During S-phase, in order to preserve cell identity, in addition to DNA information, PcG-chromatin-mediated epigenetic signatures need to be duplicated requiring a tight coordination between PcG proteins and replication programs. However, the interconnection between replication timing control and PcG functions remains unknown. Using Drosophila embryonic cell lines, we find that, while presence of specific PcG complexes and underlying transcription state are not the sole determinants of cellular replication timing, PcG-mediated higher-order structures appear to dictate the timing of replication and maintenance of the silenced state. Using published datasets we show that PRC1, PRC2, and PhoRC complexes differently correlate with replication timing of their targets. In the fully repressed BX-C, loss of function experiments revealed a synergistic role for PcG proteins in the maintenance of replication programs through the mediation of higher-order structures. Accordingly, replication timing analysis performed on two Drosophila cell lines differing for BX-C gene expression states, PcG distribution, and chromatin domain conformation revealed a cell-type-specific replication program that mirrors lineage-specific BX-C higher-order structures. Our work suggests that PcG complexes, by regulating higher-order chromatin structure at their target sites, contribute to the definition and the maintenance of genomic structural domains where genes showing the same epigenetic state replicate at the same time.